2007
DOI: 10.1002/ptr.2059
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity of Setaria megaphylla

Abstract: The antimalarial activity of an ethanol leaf extract of Setaria megaphylla was studied in vivo in mice infected with Plasmodium berghei berghei during early and established infections. Setaria megaphylla (100-300 mg/kg/day) exhibited a significant (p < 0.05) blood schizonticidal activity in 4-day early infection and in established infection with a significant (p < 0.05) mean survival time comparable to that of the standard drug, chloroquine, 5 mg/kg/day. The leaf extract possesses a promising antiplasmodial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…They are: Cylicodiscus gabunensis (Okokon et al, 2006b), Uvaria chamae and Hippocratea africana (Okokon et al, 2006a), Enantia chlorantha and Cymbopogon giganteus (Agbaje and Onabanjo, 1991;Kimbi and Fagbenro-Beyioku, 1996), Cymbopogon citratus and Ocimum gratissimum (Tchoumbougnang et al, 2005), Cassia singueana (Adzu et al, 2003), Stachytarpheta cayennensis (Okokon et al, 2008), Striga hermonthica and Tapinanthus sessilifolius (Okpako and Ajaiyeoba, 2004), Tetrapleura tetraptera (Okokon et al, 2007b), Setaria megaphylla (Okokon et al, 2007c), Phyllanthus amarus (Dapper et al, 2007), Homalium letestui (Okokon et al, 2006c) and the plant formula 'Agbo-Iba' shown to protect mice against Plasmodium yoelii nigeriensis infection; the herbs used in this formula were decocted for 3 h and then administered to mice orally to evaluate the prophylactic and curative activities. Although the 'Agbo-Iba' formula was prophylactic and had no apparent significant side effects in mice, the formula had no curative activity against established infection (Nwabuisi, 2002).…”
Section: Scientific Authentication Of Antimalarial Activities Of Nigementioning
confidence: 99%
“…They are: Cylicodiscus gabunensis (Okokon et al, 2006b), Uvaria chamae and Hippocratea africana (Okokon et al, 2006a), Enantia chlorantha and Cymbopogon giganteus (Agbaje and Onabanjo, 1991;Kimbi and Fagbenro-Beyioku, 1996), Cymbopogon citratus and Ocimum gratissimum (Tchoumbougnang et al, 2005), Cassia singueana (Adzu et al, 2003), Stachytarpheta cayennensis (Okokon et al, 2008), Striga hermonthica and Tapinanthus sessilifolius (Okpako and Ajaiyeoba, 2004), Tetrapleura tetraptera (Okokon et al, 2007b), Setaria megaphylla (Okokon et al, 2007c), Phyllanthus amarus (Dapper et al, 2007), Homalium letestui (Okokon et al, 2006c) and the plant formula 'Agbo-Iba' shown to protect mice against Plasmodium yoelii nigeriensis infection; the herbs used in this formula were decocted for 3 h and then administered to mice orally to evaluate the prophylactic and curative activities. Although the 'Agbo-Iba' formula was prophylactic and had no apparent significant side effects in mice, the formula had no curative activity against established infection (Nwabuisi, 2002).…”
Section: Scientific Authentication Of Antimalarial Activities Of Nigementioning
confidence: 99%
“…Cynodon dactylon, commonly known as bermudagrass or arugampullu in Tamil Nadu, India, possesses various medicinal properties such as antimicrobial, antiviral activity (Dhar et al 1968). The antimalarial activity of an ethanol leaf extract of Setaria megaphylla (Poaceae) was studied in vivo in mice infected with Plasmodium berghei berghei during early and established infections (Okokon et al 2007). The roots and tubers of Gloriosa superba, an ornamental climbing herb native of tropical Asia and Africa, have been used in traditional Indian medicine for the treatment of gout, in diseases of skin, and several other purposes (Finnie and Staden 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage parasitaemia was determined by counting the number of parasitized red blood cells against the total number of red blood cells. The inoculum was prepared by diluting 2 mL of the parasitized blood with 10 mL of sterile normal saline, to obtain the final inoculum of 0.2 mL (1.0 ×10 7 ), which is the standard inoculum for the infection of a single mouse (23).…”
Section: Animalsmentioning
confidence: 99%